2020
DOI: 10.17645/pag.v8i4.3154
|View full text |Cite
|
Sign up to set email alerts
|

Doing Civil Society-Driven Social Accountability in a Disaster Context: Evidence from Post-Earthquake Nepal

Abstract: While accountability has gained significant traction within the contemporary discourse on disaster governance, what it means and takes to be ‘doing accountability’ in promoting democratic governance of disasters remain scantly understood.<em> </em>Using the concept of social accountability and drawing on an ethnographic case study of a civil society-led accountability campaign in post-earthquake Nepal (the Mobile Citizen Help Desk, or MCHD), this article shows how MCHD sought to amplify local voice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Rooted in the Constitution of Nepal, some efforts have been made to promote political commitment to more accountable and transparent governance. However, the attitudes of citizens and duty-bearers towards each other reflected the negative with entrenched power structures, creating an environment of distrust [ 41 ]. This resulted in perpetuation of the previously weak roles of both citizens and duty-bearers in the application of social accountability mechanisms to promote and improve mental health services.…”
Section: Discussionmentioning
confidence: 99%
“…Rooted in the Constitution of Nepal, some efforts have been made to promote political commitment to more accountable and transparent governance. However, the attitudes of citizens and duty-bearers towards each other reflected the negative with entrenched power structures, creating an environment of distrust [ 41 ]. This resulted in perpetuation of the previously weak roles of both citizens and duty-bearers in the application of social accountability mechanisms to promote and improve mental health services.…”
Section: Discussionmentioning
confidence: 99%
“…The 3RF secretariat was supposed to publish a website that only came to existence as we were writing this paper, over two years after the establishment of the platform. Thus, the 3RF's institutional architecture did not establish effective modalities for CSOs to fulfill their watchdog roles and uphold accountability and transparency, such as a citizen engagement platform or grievance reporting mechanisms that are usually recommended by experts (Daly and Brassard, 2011;Haigh et al, 2019;Dhungana, 2020). These shortcomings significantly constrained good governance, monitoring and progress reporting and hence effective processes of participation.…”
Section: Dpm 333mentioning
confidence: 99%
“…Although a reconstruction committee was formed at the community level, the participation of the most vulnerable people was limited. The research revealed that attempts made after the earthquake to translate citizens' voices into state responses were ineffective (Dhungana, 2020).…”
Section: Participationmentioning
confidence: 99%